Plasmon‐enhanced inelastic scattering by 2D and 3D superlattices made of silver nanocrystals. (18th October 2018) - Courty, Alexa; Bayle, Maxime; Carles, Robert
Abstract: The lattice dynamics of natural crystals, artificial superlattices, or self‐organized nanocrystals intimately mix confinement, coupling, periodicity, and dissipative effects. The low wavenumber vibrational response of the new class of nanomaterials called "supercrystals" does contain relevant information concerning finite size effects on atomic movements inside each nanocrystal, mechanical coupling between adjacent nanocrystals, coherent behavior of the total assembly due to its superperiodicity, and finally finite‐time effects due to damping. All these aspects concerning the dynamical behavior of silver supercrystals has been analyzed using plasmon resonance Raman scattering. Owing to the highly uniform size and chemical environment of the nanocrystals, the confinement and homogeneous damping of their fundamental vibrations are carefully analyzed. The signature of their internal atomic arrangements, as a reminiscence of bulk phonons, is also explored. It is shown that for low particles diameter (≲5 nm), deviations from the continuum elastic approximation occur and that the vibrational response is more sensitive to atomic arrangements and surface effects inside the nanocrystals than to spatial coherence effects between them. Abstract : Using plasmon resonance and low‐wavenumber Raman scattering from periodic arrangements of silver nanocrystals, information concerning finite size effects on atomic movements inside each nanocrystal, mechanical coupling between adjacent nanocrystals, coherent behavior of the total assembly due its superperiodicity, and finally finite‐time effects due to damping, have been analyzed. A theoretical support is given through atomic‐scale simulations.